Human task performance and associated internal states in extended reality: a systematic review of cognitive, psychophysiological, and physiological dimensions - Ahmed, Nasim; Wu, Peng; Huang, Kaiming; Jung, Sungchul; Rheem, Hansol; Tan, Gang; Imani, Mahdi; Islam, Rifatul (Frontiers in Virtual Reality, 2025)
Human task performance in extended reality (XR) environments is a critical area of study due to the growing use of these technologies in fields such as healthcare, education, manufacturing, and training, as XR has the potential to influence both how well people complete tasks (e.g., accuracy, speed) and underlying human states such as cognitive load, stress, and physiological responses. A plethora of research has explored the benefits of XR across these domains, as well as research to investigate potential negative impacts on cognition and task performance. However, the findings regarding task performance remain inconclusive, and the factors contributing to enhanced versus diminished performance are poorly defined. In this paper, we conduct a systematic literature review of 79 research papers from 2015 to 2024, following the PRISMA guidelines, selected from an initial pool of 6,878 search results from the Publish or Perish database. Our review reveals that a key gap exists in understanding how specific XR factors, such as immersion levels, interaction modalities, and user interface design, influence both task performance and associated cognitive, psychophysiological, and physiological outcomes. We also report how these different factors influence the performance of cognitive, psychophysiological, and physiological tasks in different XR environments. We conclude by proposing potential research gaps and future research directions to focus on controlled experimental studies targeting these factors to gain deeper insights into their impact on human performance in XR settings.